2021
DOI: 10.7150/jca.60694
|View full text |Cite
|
Sign up to set email alerts
|

CA724 Predicts Tumor Regression Grade in Locally Advanced Gastric Cancer Patients with Neoadjuvant Chemotherapy

Abstract: Purpose: Tumor regression grade (TRG) is widely used to evaluate the efficacy of neoadjuvant chemotherapy (NCT) and it is related to many clinicopathological factors. However, whether TRG can be predicted by clinical characteristics is unknown. Methods: 141 locally advanced gastric cancer (GC) patients who underwent NCT and curative operation were retrospectively analyzed. TRG is reevaluated according to the CAP guideline. The values of CA199, CA125 and CA724 before NCT (pre-) and after NCT (post-) were extrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…The lack of a standardized approach for reporting the pathology of lung cancer patients resected after neoadjuvant therapy could indicate that pathologists are not involved in study designs ( 21 , 32 ). We used the newer CAP/NCCN guidelines for tumor regression grading following neoadjuvant chemotherapy to evaluate postoperative pathological specimens in all cases, which increased the reliability of the study ( 33 , 34 ). Our results demonstrate that the tumor regression grade of the neoadjuvant immunotherapy group was significantly better than that of the neoadjuvant chemotherapy group.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of a standardized approach for reporting the pathology of lung cancer patients resected after neoadjuvant therapy could indicate that pathologists are not involved in study designs ( 21 , 32 ). We used the newer CAP/NCCN guidelines for tumor regression grading following neoadjuvant chemotherapy to evaluate postoperative pathological specimens in all cases, which increased the reliability of the study ( 33 , 34 ). Our results demonstrate that the tumor regression grade of the neoadjuvant immunotherapy group was significantly better than that of the neoadjuvant chemotherapy group.…”
Section: Discussionmentioning
confidence: 99%
“…CA724 is one of the novel tumor markers, which was first discovered in 1981 and is widely used in the diagnosis of breast cancer and gastrointestinal tumor diseases. CA724 has a high sensitivity in the diagnosis of GC and can be detected in all stages, and is slightly superior to other tumor markers in the diagnostic efficacy of GC[ 37 , 38 ]. The results of this study were also consistent with that.…”
Section: Discussionmentioning
confidence: 99%
“…In our research, CA724 prior to NAT was identified as an independent prognostic factor through multivariable analysis which is in agreement with the findings of Sun et al [ 25 ]. Similarly, Tong et al found CA724 prior to treatment was an independent risk factor to pathological reaction which is beneficial to predict TRG [ 26 ]. Lymph node metastases, invasion depth and vascular invasion or lymphatic invasion are independent prognostic indicators of survival in patients with GC [ 27 ].…”
Section: Discussionmentioning
confidence: 99%